2023
DOI: 10.1038/s41598-023-30316-5
|View full text |Cite
|
Sign up to set email alerts
|

PEPI Lab: a flexible compact multi-modal setup for X-ray phase-contrast and spectral imaging

Abstract: This paper presents a new flexible compact multi-modal imaging setup referred to as PEPI (Photon-counting Edge-illumination Phase-contrast imaging) Lab, which is based on the edge-illumination (EI) technique and a chromatic detector. The system enables both X-ray phase-contrast (XPCI) and spectral (XSI) imaging of samples on the centimeter scale. This work conceptually follows all the stages in its realization, from the design to the first imaging results. The setup can be operated in four different modes, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…The aim of the project is to combine the specific advantages of the detector, namely high efficiency, sharp response, and spectral capabilities, with the sensitivity to phase effects (i.e., refraction and ultra-small-angle scattering) enabled by EI. In order to define the optimal design of the experimental setup, a novel publicly available Geant4-based simulation platform (Geant4PEPI) has been developed [8]. Within this tool phase effects are simulated through a custom X-ray refraction process, that is not included in the available Geant4 releases, and an EI experimental setup is replicated including realistic source spatial and spectral distributions, geometry and compositions of samples and absorbing masks, and image acquisition procedures [9].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the project is to combine the specific advantages of the detector, namely high efficiency, sharp response, and spectral capabilities, with the sensitivity to phase effects (i.e., refraction and ultra-small-angle scattering) enabled by EI. In order to define the optimal design of the experimental setup, a novel publicly available Geant4-based simulation platform (Geant4PEPI) has been developed [8]. Within this tool phase effects are simulated through a custom X-ray refraction process, that is not included in the available Geant4 releases, and an EI experimental setup is replicated including realistic source spatial and spectral distributions, geometry and compositions of samples and absorbing masks, and image acquisition procedures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Raw projection images acquired at different positions of the illumination curve were processed via GPU-based Gaussian fitting to retrieve attenuation and differential phase signals (Przybylski et al 2017 , Brombal et al 2023a ). Integral phase projections were obtained from the differential phase via a Wiener-filter regularized phase-integration algorithm (Massimi et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it is clear that the combination of spectral and phase-contrast techniques would bring both high visibility of low- Z biological tissues and effective separation of high- Z materials (contrast media). So far, due to the limited availability of phase-contrast systems equipped with spectral detectors, only a relatively small number of spectral phase contrast studies have been reported in the literature (Mechlem et al 2019 , Schaff et al 2020 , Astolfo et al 2023 , Brombal et al 2023a ). The most illustrative example is arguably the one provided by Ji et al ( 2020 ) where a GI system is coupled with a 100 μ m pixel size photon-counting detector.…”
Section: Introductionmentioning
confidence: 99%
“…As for other XPCI techniques, SBI has been first performed using coherent synchrotron sources. However, XPCI techniques can be adapted to laboratory facilities with quasi-coherent (micro-focus) sources, as reported in the literature [5][6][7]. To obtain optimal results in SBI, it is crucial to ensure the visibility of the speckles.…”
Section: Introductionmentioning
confidence: 99%